Molecular masses and characteristics of polyethileneglycolmaleate, polypropyleneglycolmaleate, polyethileneglycolphthalate, polypropyleneglycolphthalate - Sarsenbekova, A.Zh.; Zhortarova, E.A.; Burkeev, M.Zh.; Tazhbaev, E.M.; Kazhmuratova, A.T. (KSU Publ., 2014)
The molecular masses and characteristics of such unsaturated polyester resins as polyethyleneglycolmaleate, polypropyleneglycolmaleate, polyethyleneglycolphthalate and polypropyleneglycolphthalate were studied. It was determined the weight average molecular weight and number average molecular weight of unsaturated polyester resins, and it was carried out the comparative analysis of the obtained data.
Полиэтиленгликольмалеинат, полипропиленгликольмалеинат, полиэтиленгликольфталат жəне полипропиленгликольфталаттың сипаттамасы жəне молекулалық массалары
Молекулярные массы и характеристики полиэтиленгликольмалеината, полипропиленгликольмалеината, полиэтиленгликольфталата и полипропиленгликольфталата
Keywords: unsaturated polyester resin; number-average molecular weight; weight-average molecular weight